ANALISIS PENGARUH INFLASI, SUKU BUNGA, DAN NILAI TUKAR TERHADAP KINERJA KEUANGAN SEKTOR PANGAN DI BURSA EFEK INDONESIA (BEI) PERIODE 2019-2022 - Nadilla Anggreini; Zulfa Irawati (Jurnal Ekonomika: Manajemen, Akuntansi, dan Perbankan Syari'ah, 2024)
Company performance is referred to as a description of the financial condition of a company which is analyzed by financial analysis tools, so that it can be known whether the good and bad financial condition of a company reflects work performance in a certain period. This is very important so that resources can be used optimally in the face of environmental changes. The purpose of this study was to analyze the effect of inflation, interest rates, and exchange rates on the financial performance of the food sector on the Indonesia Stock Exchange (IDX) for the 2019-2022 period. This type of research is quantitative, quantitative data in this study are data on inflation rates, interest rates, and exchange rates. The population is food sub-sector companies listed on the Indonesia Stock Exchange (IDX). The technique of determining the sample with purposive sampling. The samples used are several companies engaged in the food sector. The data analysis technique used is quantitative analysis expressed by numbers and calculations using Microsoft Excel and SPSS23 (Statistical Program For Social Science) with the Multiple Regression Statistical analysis method. The results of this study that the inflation rate, interest rates, exchange rates show a positive and significant effect on financial performance in companies listed on the IDX for the 2019-2022 period.